The sensitivity of murine spermiogenesis to miglustat is a quantitative trait: a pharmacogenetic study. - Bone, W; Walden, C; Fritsch, M; Voigtmann, U; Leifke, E; Gottwald, U; Boomkamp, S; Platt, F; van der Spoel, A (2007)
BACKGROUND: A major event in the post-meiotic development of male germ cells is the formation of the acrosome. This process can be perturbed in C57BL/6 mice by administration of the small molecule miglustat (N-butyldeoxynojirimycin, NB-DNJ). The miglustat-treated mice produce morphologically abnormal spermatozoa that lack acrosomes and are poorly motile. In C57BL/6 mice, miglustat can be used to maintain long-term reversible infertility. In contrast, when miglustat was evaluated in normal men, it did not affect spermatogenesis. To gain more insight into this species difference we have now evaluated the reproductive effects of miglustat in rabbits, in multiple mouse strains and in interstrain hybrid mice. METHODS: Male mice of 18 inbred strains were administered miglustat orally or via miniosmotic pumps. Rabbits were given the compound in their food. Fourth-generation interstrain hybrid mice, bred from C57BL/6 and FVB/N mice (which differ in their response to miglustat), also received the drug. Data on fertility (natural mating), sperm motility and morphology, acrosome status, and serum drug levels were collected. RESULTS: In rabbits the drug did not induce aberrations of sperm shape or motility, although the serum level of miglustat in rabbits far exceeded the level in C57BL/6 mice (8.4 microM and 0.5 microM, respectively). In some strains of the Swiss and Castle lineages of inbred mice miglustat did not cause infertility, severe morphological sperm aberrations or reduced sperm motility. In these strains miglustat only had milder effects. However, miglustat strongly disturbed acrosome and sperm nucleus development in AKR/J and BALB/c mice and in a number of C57BL/6-related strains. The consequences of drug administration in the interstrain hybrid mice were highly variable. Judging by the number of grossly abnormal spermatozoa, these genetically heterogeneous mice displayed a continuous range of intermediate responses, distinct from either of their parental strains. CONCLUSION: The effects of miglustat on spermatogenesis in mice are strain-dependent, while in rabbits the drug is ineffective. Evaluation of interstrain hybrid mice indicated that the sensitivity of spermatogenesis to miglustat is a quantitative trait. These studies pave the way for identifying the genetic factors underlying the strain/species differences in the effect of miglustat.